Preliminary Study of Fish Abundance and Size in Intertidal Waters Around Unsrat Likupang Laboratory of North Minahasa Regency - Ariesta Akbar Martino; Nego E. Bataragoa; Leonardo J. Tombokan (Sam Ratulangi University, 2017)
Fish that migrate to tidal areas are usually dominated by the juvenile phase. This research was conducted in order to know the abundance and variation of species that present in the intertidal water areas around Likupang Field Laboratory. Sampling for data was conducted by using a coastal net during the new moon, quater and full moon phase in the months of October and November 2016. The species abundance was calculated based on the Importance Value Index (IVI) formula, length variation and length frequency distribution. During the field study, 723 individuals were recorded that belong to 93 species. The species abundance calculations, based on the important value index (IVI), were found ranging from 6.90% to 0.38%. It was recorded also that there are 3 species with relatively higher IVI score i.e Chelonodon patoca (6.90%), Paraplotosus albilabris (4.74%) and Caranx melampygus (3.75%). The variations in the size among migratory fish are generally abserved in the juvenile phase, except for some species such as Ambassador urotaenia, Plotosus lineatus, Taeniura lymma, and Terapon jarbua that reach adult size.Keywords: juvenile phase, abundance, size variation, important value indexÂ ABSTRAKIkan yang bermigrasi ke daerah pasang-surut biasanya didominasi pada fase juvenile. Penelitian ini dilakukan dengan tujuan untuk mengetahui kelimpahan spesies dan variasi ukuran spesies yang ada di daerah intertidal sekitar Laboratorium Basah Likupang. Pengambilan sampel dilakukan dengan menggunakan jaring pantai pada fase bulan baru, kwartir dan purnama pada bulan oktober dan November tahun 2016. Kelimpahan spesies di analisis dengan pendekatan Indeks Nilai Penting (INP), Variasi Ukuran Panjang dan Distribusi Frekuensi Panjang. Selama penelitian didapat 723 individu dari 93 spesies. Kelimpahan spesies berdasarkan indeks nilai penting (INP) berkisar antara 6,90% sampai 0,38%. Terdapat 3 spesies dengan nilai INP relatif besar yaitu Chelonodon patoca (6,90%), Paraplotosus albilabris (4,74%) dan Caranx melampygus (3,75%). Variasi ukuran ikan yang bermigrasi umumnya adalah ikan dalam fase juvenile, kecuali beberapa spesies yang mencapai ukuran dewasa seperti Ambassis urotaenia, Plotosus lineatus, Taeniura lymma, Terapon jarbua.Kata kunci : Fase juvenile, Kelimpahan, Variasi ukuran, Indeks Nilai Penting